Integrated stratigraphy of the Priabonian (upper Eocene) Urtsadzor section, Armenia - Cotton, Laura J.; Zakrevskaya, Elena Y.; van der Boon, Annique; Asatryan, Gayane; Hayrapetyan, Flora; Israyelyan, Arsen; Krijgsman, Wout; Less, György; Monechi, Simonetta; Papazzoni, Cesare A.; Pearson, Paul N.; Razumovskiy, Anatoly; et al. (Newsletters on Stratigraphy, 2016)
The transition from the Bartonian to the Priabonian, as traditionally understood, has long been associated with a series of extinctions and originations in several microfossil groups. The planktonic foraminifer genus Morozovelloides and large species of Acarinina suffered a rapid global extinction, as did many radiolarians. Calcareous nannofossils show several assemblage changes including the acme beginning of Cribrocentrum erbae and the lowest and highest occurrences of Chiasmolithus oamaruensis and C. grandis respectively. In shallow water environments, larger foraminifera also show an extinction among large species of Nummulites, as well as the first occurrences of the stratigraphically important genus Spiroclypeus. However, the correlation between shallow and deep water records remains uncertain, as do the mechanisms driving these biotic events. Here we present the results of a new integrated stratigraphical study (calcareous nannofossils, planktonic foraminifera, larger benthic foraminifera, and low-resolution magnetostratigraphy) of the Urtsadzor section in south-western Armenia which appears to be continuous through this interval. The Urtsadzor section consists of calcareous siltstones rich in micro- and nannofossils, with interbedded limestones containing abundant larger benthic foraminifera. Our new data enable us to correlate larger foraminiferal events with global plankton biostratigraphy, in a section outside of southwest Europe where most previous correlations have been based. At Urtsadzor, the large Nummulites species of N. millecaput-group are present throughout the whole section but decrease in abundance toward the top. The first occurrence of Spiroclypeus, also occurs in the upper part of the section, marking the SBZ 18/19 boundary. These events are associated with the phylogenetic development of the Nummulites fabianii and Heterostegina reticulata lineages. However, the calcareous plankton biostratigraphy indicates the section is well within the Priabonian; within planktonic foraminiferal Zones E14 and E15 and calcareous nannoplankton Zones CNE 18 and CNE 19. These results indicate larger foraminiferal events occur well above the planktonic foraminiferal extinction level and nannofossil assemblage changes indicating the events are not synchronous across groups, with implications for biostratigraphy and recognition of the basal Priabonian in different depositional settings and regions.